2021
DOI: 10.1038/s41427-021-00297-w
|View full text |Cite
|
Sign up to set email alerts
|

Functional tissue-engineered bone-like graft made of a fibrin scaffold and TG2 gene-modified EMSCs for bone defect repair

Abstract: The transplantation of tissue-engineered scaffolds with stem cells is a promising therapeutic approach for bone defect repair. To improve the therapeutic efficacy of this approach, in this study, a novel biofunctional live tissue-engineered bone-like graft was designed and constructed using a fibrin scaffold loaded with TG2 gene-modified ectomesenchymal stem cells (TG2-EMSCs) derived from nasal respiratory mucosa for bone defect repair. Autocalcification of the cell-free fibrin gel in osteogenic medium with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…TG2 has been identi ed as an important extracellular crosslinking enzyme involved in ECM turnover and bone differentiation [44]. As shown in our previous study, TG2 overexpression enhances the osteogenic differentiation of EMSCs, partially through crosslinking ECM and BMP-2 [6]. Using various cell lines, Fisher and Liu showed that TG2 is directly regulated by YAP [39,40]; by upregulating TG2 expression, YAP probably forms a positive feedback loop.…”
Section: Yap Promotes Emsc Osteogenic Differentiation By Upregulating Tg2mentioning
confidence: 71%
See 3 more Smart Citations
“…TG2 has been identi ed as an important extracellular crosslinking enzyme involved in ECM turnover and bone differentiation [44]. As shown in our previous study, TG2 overexpression enhances the osteogenic differentiation of EMSCs, partially through crosslinking ECM and BMP-2 [6]. Using various cell lines, Fisher and Liu showed that TG2 is directly regulated by YAP [39,40]; by upregulating TG2 expression, YAP probably forms a positive feedback loop.…”
Section: Yap Promotes Emsc Osteogenic Differentiation By Upregulating Tg2mentioning
confidence: 71%
“…EMSCs were isolated from rats as described in our previous studies [6]. Brie y, two rats (50-80 g) were sacri ced by administering pentobarbital sodium (200 mg/kg).…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Besides, EMSCs are self-renewable with multidirectional differentiation potential, which have been thoroughly characterized in our previous studies [ 16 , 17 ]. We have proved that EMSCs can differentiate into several cell lineages including adipocytes, neurocytes, chondrocytes and osteocytes [ 18 , 19 ]. These special properties render EMSCs as a promising tool for exploring potential molecular mechanisms that modulate the osteogenic differentiation of EMSCs by chemical signals, including BPs.…”
Section: Introductionmentioning
confidence: 99%